Analyzing the Readability of Online Urogynecologic Patient Information. Issue 1 (January 2019) - Stewart, J. Ryan; Heit, Michael H.; Meriwether, Kate V.; Hobson, Deslyn T.; Francis, Sean L.
Abstract : Objective: We sought to describe the readability of Web sites arising from the most common Google search terms related to pelvic organ prolapse, bladder control, and bowel control. Methods: Google was queried to capture the top 100 search results for the keywords in each disease group. For the top 20 results of each keyword, we analyzed the text for readability using 4 readability formulas: Dale-Chall, Gunning-Fog, Simple Measure of Gobbledygook (SMOG), and Flesch-Kincaid Grade Level. Readability scores were compared using 1-way analysis of variance (α = 0.05), and the Tukey test was performed to characterize any significant differences. The χ 2 tests were used to compare results above and below the eighth grade reading level. Spearman correlations were used to compare the reliability of the different readability formulas. Results: We evaluated 2731 unique Web sites for readability, of which 2334 (85%) had a SMOG score at or above an eighth grade reading level. The mean SMOG score was 9.7 ± 2.1. Web sites in the bladder control keyword group had statistically higher SMOG scores than those in the bowel control and pelvic organ prolapse groups, with means of 9.9 ± 2.0, 9.4 ± 2.1, and 9.6 ± 2.0, respectively. The SMOG was found to be the most reliable. Conclusions: The vast majority of urogynecologic information available to patients on the Internet is written at or above an eighth grade reading level despite longstanding recommendations to the contrary. Clinicians should advise patients that the information they find online may be difficult to understand. Abstract : A review of 2731 urogynecology-related Web pages shows 85% are above the National Institutes of Health–recommended eighth grade reading level.